Applying the NIMHD research framework to assess research capacity: lessons and adaptations for use - Shelby L. Langer; Aliria M. Rascón; Heather M. Ross; Julia F. Hammett; Alyssa G. Robillard; Angel B. Algarin; Felipe Gonzalez Castro; Fiorella L. Carlos Chavez; Joseph Daniels; Kelly C. Davis; Rachel Gur-Arie; Rodney P. Joseph; et al. (Frontiers in Public Health, 2026)
The National Institute on Minority Health and Health Disparities Research Framework illustrates that health and health disparities are shaped by a complex interplay of factors that operate across multiple domains and levels of influence. We sought to apply the framework in a novel way, to examine and inform the collective work of an academic research center focused on health promotion and disease prevention. Center investigators independently mapped their research onto a grid crossing five domains (biological, behavioral, physical/ built environment, sociocultural environment, healthcare system) and four levels of influence (individual, interpersonal, community, societal). We describe and reflect on two mapping exercises as a use case to strengthen practical application of the framework for research planning and evaluation. We also highlight key questions that emerged during implementation and propose potential adaptations to improve the framework’s utility for interdisciplinary teams working to address health disparities.